Risk of Hepatitis B and Hepatitis C Among Whole Blood Transfused Chronic Hemodialysed Chronic Kidney Disease (CKD) Patients - Quader, Md Abdul; Islam, Khan Anisul; Dipta, Tashmim Farhana; Islam, Md Ashadul (Bangladesh Journal of Medicine, 2019)
Background: Patients with chronic renal failure on maintenance hemodialysis (MHD) have high risks of viral infections and the prevalence of transfusion transmissible viral infection is common among them. The aim of our study was to detect hepatitis B and hepatitis C virus in hemodialysis patients and healthy donors and to explore if there was a relationship between duration of hemodialysis and hepatitis B and hepatitis C in our patients. Methodology: A cross sectional study was conducted in a private hemodialysis clinic in Dhaka city with end stage renal disease on maintenance hemodialysis and an age matched healthy donors as comparable group from July 2015 to June 2016. Serum alanine aminotransferase (ALT), serum aspartate aminotransferase (AST), HBsAg and anti HCV were determined along with duration and units of blood transfusion needed by them. Results: Our study showed the mean age of 126 MHD patients were 42.2±11.7 years along with 132 healthy donors as control group had mean age 39.2±9.7 years. Among the hemodialysis patients 34 (26.98%) showed transfusion transmitted infection positivity and in control group 11 (8.33%) showed transfusion transmitted infection positivity with the difference between two study group showed statistical significance (p<o.oo1). History of blood transfusion showed the significant predictor of occurrence of TTV infection in hemodialysis patients (p<0.01). Duration of hemodialysis and seropositivity of TTI was not significant (p>0.05). The number of units of blood transfusion and the TTI positivity also showed no significant difference (p>0.05) with HBsAg (17.46%) and anti HCV (9.52%). Conclusions: The prevalence of TTI in hemodialysis patients is significantly higher than that in healthy individuals. So, the regular screening of HBV and HCV among patients and healthy donors are strictly provided to monitor the communicable disease. Bangladesh J Medicine July 2019; 30(2) : 78-82